A Comparative Study of Natural Sciences as a Miracle and Natural Laws: A Case of Historical Linguistics - Barati, Farajollah; Divani, Amir; Javadi, Mohsen; Ali Zamani, Amir Abbas (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
<!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–> This study investigated the comparison of instructing natural sciences as a miracle and natural laws through the comparative linguistic process from Eastern and Western scholars perspectives. This study may provide some evidence on the problems the teachers face in designing a new method of using cause and effect processes speaking skills. This may help the English language learners to follow these processes in speaking and class discussions in a comparative study of Western and Eastern approaches to class discussion. The method of this study was based on historical design. The participants filled in a researcher-made questionnaire to compare their views on the two major schools of Eastern and Western thoughts referring to the schools contributions to teach causality. Data were analyzed and the results showed that both schools have relied on their background perspectives on religious thoughts. Therefore, the main findings of this study focuses on the compromise of East and West to make a unique method in instructing cause and effect processes. <!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–>